Perlindungan Data Pribadi dalam Teknologi AI: Analisis Peran Hukum dan Kepatuhan Regulasi Bisnis Digital - Tri Vebri Yance; Agus Setiawan; Rahmi; Amaliah Khairunissa (Jurnal Ilmu Hukum, 2025)
Personal data protection. This study aims to examine in depth the legal role in regulating the use of AI that processes personal information, as well as to analyze the compliance challenges faced by business actors in meeting data protection standards. Employing a normative juridical approach supported by literature review, this research evaluates data management principles oriented toward transparency, consent, technical security, and the accountability of electronic system providers. The findings indicate that the inadequacy of legal infrastructure, low levels of privacy literacy, and weak oversight mechanisms have created an imbalance between technological innovation and the protection of data subjects’ rights, thereby increasing vulnerabilities to data breaches and potential legal consequences for businesses. This study affirms that strengthening internal policies, implementing auditing mechanisms, and adopting data protection technologies constitute essential instruments for ensuring ongoing compliance. Accordingly, adaptive legal responses and ethically oriented data governance are crucial prerequisites for creating a secure, accountable, and sustainable digital ecosystem in the use of AI technologies..